Relative Accuracy of Some Methods of Harmonic Analysis of Tides - Franco, A. Dos Santos (The International Hydrographic Review, 2015)
In this study we seek to establish the relative accuracy of some methods of harmonic tidal analysis, involving observations of a month’s duration. It is obvious that the developments which we shall make will be of an entirely general character; however we shall here limit ourselves to shortperiod analyses.